A study of infectious endocarditis in Ribeirão Preto, SP - Brazil. Analysis of cases occurring between 1992 and 1997 - Ruiz Jr,Everaldo (2000)
OBJECTIVE: To analyze the epidemiology, diagnosis, clinical aspects causes and evolution of infectious endocarditis. METHODS: The patients analyzed were treated at the University Hospital of the Faculdade de Medicina of Ribeirão Preto-USP and had a diagnosis of infectious endocarditis defined by Duke's criteria, which classifies infectious endocarditis as native, prosthetic valve or that occurring in intravenous drug users. RESULTS: One hundred and eighty episodes of infectious endocarditis in 168 patients were observed. Echocardiograms in 132 (73.3%) provided a diagnosis of infectious endocarditis in 111 (84%) patients; mitral valves were affected in 55 (30.5%), tricuspid valves in 30 (16.6%) and the aortic valve in 28 (15.5%) patients. Hemocultures were performed in 148 (93.8%) episodes of IE. The most commonly isolated infectious organisms were Staphylococcus aureus in 46 (27.2%) patients and Streptococcus viridans in 27 (15.9%). Complications occurred in 116 (64.4%) patients and 73 (40.5%) of the patients died. CONCLUSION: The general profile of the observed infectious endocarditis was similar to that reported in studies performed in other countries and included users of intravenous drugs. The high degree of mortality observed is not compatible with progress in diagnosis and treatment of infectious endocarditis and is probably due to the absence of diagnostic suspicion. The high frequency of fatal cases of septicemia (45.1% of deaths) in the patients studied indicates that unnoticed cases of infectious endocarditis had only been diagnosed at necropsy.